(untitled) (Research, Society and Development, 2022)
Natural extracts are described in the literature as biomolecules that have, among others, antioxidant and photoprotective properties. In addition, other advantages allow its use, such as low toxicity and high biodegradability. The skin is an organ that is constantly exposed to oxidative stress, including ultraviolet (UV) radiation, air pollutants and chemicals. These factors directly lead to premature skin aging. The interest in active substances from Brazilian biodiversity, especially the Caatinga Biome, highlighting the attention and research of the pharmaceutical sector and cosmetic industries, to study the insertion of natural biomolecules of plant origin, to demonstrate to consumers the safety and efficacy of these products. However, the objective of this review is to present plants from the Brazilian Caatinga that have biological activities that act in the preventive process of skin care and that have potential for the production of phytocosmetics. This integrative review was produced through a search carried out from January to April 2022. This bibliographic search was carried out in specialized databases (PubMed, Scopus and Science Direct), the manuscript selection was based on the inclusion criteria: articles with studies of plants collected in the region of the Caatinga Biome for the development or tests for skincare in the cosmetic area (in vivo and/or in vitro) with natural extracts that contain keywords in the title, abstract or full text, in the years between 2010 and 2022. Presenting results for the antioxidant, photoprotective and cytotoxicity assays of plants of the Arecaceae family.